GAMBARAN PENGETAHUAN IBU TENTANG MENYIKAT GIGI ANAK 6-12 TAHUN DI POLI GIGI PUSKESMAS - Habibah Nurul Aini; Irwan Supriyanto; Devy Octaviana; Eliza Herijulianti (Jurnal Terapi Gigi dan Mulut, 2022)
Health Teeth and mouth are very important for everyone, but there are still many people who still ignore it and think that dental and oral health are trivial things. This is related to the mother's knowledge about brushing teeth. This study aims to describe the mother's knowledge about brushing teeth in children aged 6-12 years in the dental polyclinic of Tanjungsari Public Health Center, Sumedang Regency. This research is descriptive quantitative with Questionnaire method. The research was carried out at the Dental Polyclinic of Tanjungsari Public Health Center, Sumedang Regency. The study was conducted on mothers who have children aged 6-12 years with a sample of 28 respondents who were determined using the slovin formula. Primary data obtained from the questionnaire will be presented in the form of a frequency distribution table with the results of the study showing knowledge about brushing teeth as a whole, namely 21.4% of respondents have good criteria, 46.4% have sufficient criteria, and 32.1% have poor criteria. Although almost most mothers who have children aged 6-12 years have sufficient knowledge of the criteria, there are still some who have less criteria. In order to achieve optimal dental and oral health, the knowledge of brushing teeth at the dental clinic at the Tanjungsari Public Health Center needs to be improved through various efforts, one of which is by providing counseling about brushing teeth.